Upaya Meningkatkan Kompetensi Pedagogik dalam Menyusun RPP Melalui Workshop Guru Kelas SD Binaan Kecamatan Benua Lima Kabupaten Barito Timur - Yulianti Yulianti (Jurnal Simki Postgraduate, 2022)
The purpose of this school action research is to increase teacher competence in preparing lesson plans through workshops for Class Teachers of Fostered Elementary Schools, Benua Lima District, East Barito Regency, in preparing lesson plans that are in accordance with the competency standards of each lesson so that they can become a reference in the learning process so that students able to achieve the minimum completeness criteria. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and reflection. The results showed that (1) in the formulation component of learning objectives indicators, there was an increase from 61.3% in initial competence to 69.3% in cycle I and cycle II to 73.3%; (2) In the component of determining learning materials and materials, there was an increase in competence from 464.0% to 70.7% after cycle I and in cycle II it was stronger to 72.0%; (3) In the strategy and learning method selection component, which includes learning steps and determining the time allocation used, there is a significant increase from the initial 53.3% to 62.7% in cycle I and increased again to 72.0% after cycle II; (4) Even though there was no sharp increase, there was also an increase in the selection of media and learning tools from 53.3% at the beginning of the activity and 61.3% after cycle I to 70.7% after cycle II; (5) We can also see a significant increase in the learning evaluation planning component. From initially only 46.6% at the beginning of the activity, it became 60.0% at the end of cycle I and managed to reach 74.7% at the end of cycle 2; and (6) Looking at the data obtained from research results in this school's action research activities, it can be concluded that the Workshop can improve Teacher Competence in Preparing RPP for Class Teachers of Fostered Elementary Schools, Benua Lima District, East Barito Regency.